2006
DOI: 10.1039/b517105a
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of pesticide methomyl: determination of the reaction pathway and identification of intermediate products

Abstract: The degradation of pesticide methomyl in aqueous solution by UV-irradiation in the presence of TiO2 "Degussa P-25" has been studied. It was found that mineralisation to carbon dioxide, water, sulfate and ammonia took place during the process. The rate of photodecomposition of methomyl was measured using high performance liquid chromatography (HPLC), while its mineralization was followed using ion chromatography (IC), and total organic carbon (TOC) analysis. The identification of reaction intermediate products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 10 publications
2
43
0
2
Order By: Relevance
“…Moreover, taking into consideration the complex nature of photocatalysis and the wide variety of stable and unstable photoproducts that can be formed, rate of TOC reduction depended on the individual tested organophosphate. The same behavior has been observed in numerous irradiated pesticide solutions reported in the available literature; for instance, the formation and evolution of several carboxylic acids (such as formic, acetic, glycolic, and cyanuric acids) as transient intermediates of photocatalytic reaction, which could eventually undergo complete mineralization as irradiation progresses, have been published [4,5,9,21]. Formation of oxon derivatives (such as paraoxon ethyl, pirimiphos-oxon, fenthion-oxon), corresponding phenols (e.g., nitrophenol), various and different trialkyl and dialkyl phosphorothioate or phosphate esters, and quinonidal compounds has also been observed and detected as major intermediate photoproducts that subsequently underwent mineralization [5].…”
Section: Toc Contentmentioning
confidence: 49%
See 1 more Smart Citation
“…Moreover, taking into consideration the complex nature of photocatalysis and the wide variety of stable and unstable photoproducts that can be formed, rate of TOC reduction depended on the individual tested organophosphate. The same behavior has been observed in numerous irradiated pesticide solutions reported in the available literature; for instance, the formation and evolution of several carboxylic acids (such as formic, acetic, glycolic, and cyanuric acids) as transient intermediates of photocatalytic reaction, which could eventually undergo complete mineralization as irradiation progresses, have been published [4,5,9,21]. Formation of oxon derivatives (such as paraoxon ethyl, pirimiphos-oxon, fenthion-oxon), corresponding phenols (e.g., nitrophenol), various and different trialkyl and dialkyl phosphorothioate or phosphate esters, and quinonidal compounds has also been observed and detected as major intermediate photoproducts that subsequently underwent mineralization [5].…”
Section: Toc Contentmentioning
confidence: 49%
“…Nowadays, among the most promising and successful applications of heterogeneous photocatalysis applied for the removal of various toxicants from water, photocatalysis over titanium dioxide (TiO 2 ) is included, since it has been demonstrated as one of the most frequently used methodologies employed for the treatment of chlorinated phosphate esters and carbamic, thiocarbamic, and triazine pesticides [4][5][6][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate, Malato et al ( 2002 ) found that methomyl solutions at either pH 2.7 or pH 5 did not signi fi cantly degrade via hydrolysis after 20 days; Tamimi et al ( 2006 ) later veri fi ed this result at pH 6 as well. The authors of both studies concluded that hydrolysis does not occur to any signi fi cant extent in the fi eld-at least under mildto-strong acidic conditions.…”
Section: Abiotic Processesmentioning
confidence: 76%
“…A brief summary showing the starting material and by-products under photolytic condition is shown below in Chart 2. Konstantinou et al, 2001a;Pelizzetti et al, 1990Pelizzetti et al, , 1992aPelizzetti et al, , 1992bMinero et al, 1996;Muszkat et al, 1995;Sanlaville et al, 1996, Sleiman et al, 2006 Aniline and Amide derivative Amines, Dechlorinated, Dealkylated, Cyclized, Aliphatics, Cyclized Konstantinou et al, 2001bKonstantinou et al, , 2002Sakkas et al, 2004;Peñuela and Barceló, 1996;Pathirana & Maithreepala, 1997 7 Thicarbamate derivative Amine, Carboxy, Sulfoxide, Dealkylated Vidal et al, 1999;Sturini et al, 1996;Vidal & Martin, 2001 8 Phenoxy-acids derivatives Hydroxylated, Carboxylated, Chlorophenols, Quinonidal Herrmann et al, 1998;Topalov et al, 2000;Barbeni et al, 1987;Poulios et al, 1998;9 Organophosphorus derivatives Hydroxy, Oxon, Phenol, Dialkylated, Trialkyl esters, Fragmented products Herrmann, 1999;Konstantinou et al, 2001a, Oncescu et al, 2010Herrmann et al, 1999;Hua et al, 1995;Sakkas et al, 2002;Dominguez et al, 1998 10 Carbamate derivative Hydroxylated, Decarboxylated, Phenolic, Dealkylated, Cyclized Tamimi et al, 2006;Percerancier et al, 1995;Pramauro et al, 1997;Tanaka et al, 1999;Marinas et al, 2001;Bianco Prevot et al, 199...…”
Section: Characterization Of Intermediate Productsmentioning
confidence: 99%